Spermatogenesis Duration on Adult Javan Langur (Trachypithecus auratus) Based on Testosteron Hormone and Luteinizing Hormone (LH) - Sangen, Olea Rody; Firmawati, Aulia; Marhendra, Agung Pramana Warih; Titisari, Nurina (Universitas Airlangga, 2021)
This study aimed to determine the duration of the process of spermatogenesis in adult Javan langurs (Trachypithecus auratus) by measuring levels of the hormone testosterone and luteinizing hormone (LH), as one of the efforts to increase the success of mating this endemic animals. Two Javan langurs aged 3-5-year-old, named Luki and Moses were taken their feces for 30 days. Feces extraction process used PBS with a ratio of 1: 9, while the measurement of hormone levels used Monkey Luteinizing Hormone ELISA BT Lab brand with Cat.No E0052MK for LH and Cat No E0008MK for testosterone. Hormone consentration data was a graph with fluctuating patterns which are then analyzed descriptively. The results of this study were the concentration of the hormone testosterone is in the range of 4.81 ng / gram of feces to 15.08 ng / gram of feces. While LH level is in the range of 12.59 mIU/gram to 26.24 mIU/gram. In conclusion, we could estimated that the duration of the spermatogenesis cycle every month in langur Luki occurs for 14 days, while Langur Moses for 10 days.